Indicators to Assess Digital Competence of Teachers in Initial Training in the Chile - Uruguay Contex - Silva-Quiroz, J; Miranda-Arredondo, P (UNIV EXTREMADURA, FAC EDUCACION, 2016)
The teacher is a relevant factor for inserting Information and Communication Technology (ICT) in education. Teachers are required to develop Digital Competence for Teachers (DCT), to use ICT in improving teaching and learning experiences, in addition to promoting digital competences development in girls, boys and young people. DCT should be developed from the beginning of Initial Teacher Training (ITT) for future teachers to successfully include them in the future exercise of their profession. This article presents the preliminary results of the project "Compared Study of Digital Competencies to Learn and Teach, of Teachers in Training in Chile and Uruguay." Its objective is to design, validate and apply an instrument to measure DCT in ITT in Chile and Uruguay, to compare results and recommendations to improve training for future teachers of this area. This first stage enabled generating a matrix of indicators as the foundation to build this instrument. The proposed methodology included collecting, organizing and critical assessment as part of the documental investigation. This information was used to design and validate a proposed matrix of indicators to assess DCY in ITT validated by experts in Chile and Uruguay. It includes a total of 14 indicators in four dimensions, achieving relevance of over 75%.